Analisis Penerjemahan Novel “Keledai yang Bijak” dari Novel Berbahasa Arab “Himar Al-Hakim” Karya Taufiq Al-Hakim - Chilwina, Nadhita; Surur, Misbahus (STIQ Amuntai, 2025)
Studies on translation techniques are still limited, even though this aspect plays a crucial role in producing accurate, acceptable, and understandable translations, especially for language learners. This study aims to describe the forms of translation techniques in the novel